Technological interventions and facial emotional recognition in autism spectrum disorders - Alves, Samanta (2021)
Individuals with Autism Spectrum Disorders (ASD) have deficits in the recognition of facial expressions when compared with typically developing population (Begger et al., 2006 & Deruelle et al., 2004). Computer training and multi-technology have been shown to be successful in teaching emotional skills to children with autism (Golan & Baron-Cohen, 2006; Silver & Oakes, 2001; Tanaka et al., 2010). We can find numerous educational technological resources that aim to teach facial recognition to people with ASD, but few present empirical validation of results. The majority of these techniques are non-standardized material, with no reference to research work (Ryan & Charragáin, 2010).